2009
DOI: 10.1111/j.1365-3040.2009.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant–rhizobacteria interactions alleviate abiotic stress conditions

Abstract: Root-colonizing non-pathogenic bacteria can increase plant resistance to biotic and abiotic stress factors. Bacterial inoculates have been applied as biofertilizers and can increase the effectiveness of phytoremediation. Inoculating plants with non-pathogenic bacteria can provide 'bioprotection' against biotic stresses, and some root-colonizing bacteria increase tolerance against abiotic stresses such as drought, salinity and metal toxicity. Systematic identification of bacterial strains providing cross-protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
448
1
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 821 publications
(471 citation statements)
references
References 127 publications
8
448
1
14
Order By: Relevance
“…Plant growth-promoting bacteria (PGPB) exert beneficial effects on various plants and play an important role in plant growth promotion, biological control and also resistance to abiotic stress [1][2][3]. PGPB promote growth of plants in a variety of environments by direct and indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth-promoting bacteria (PGPB) exert beneficial effects on various plants and play an important role in plant growth promotion, biological control and also resistance to abiotic stress [1][2][3]. PGPB promote growth of plants in a variety of environments by direct and indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects provoked by endophytes result from nitrogen fixation, phytohormone production, supply of nutrients and pathogen suppression (Rosenblueth and Martinez-Romero 2006;Hardoim et al 2008) and those mechanisms also account for the alleviating effects of microorganisms when host plants face unfavourable environmental conditions. Two recent reviews are devoted to the protective microbial processes conferring abiotic stress tolerance to plants (Dimkpa et al 2009;Dodd and Perez-Alfocea 2012). Halophytic plants harbour a variety of micro-organisms and in the following we summarise the contribution of micro-organisms to salt tolerance in this specific plant group.…”
Section: Influence Of Micro-organisms On Salinity Tolerance Of Halophmentioning
confidence: 99%
“…The response of plants to salinity depends on several factors such as developmental stage, severity, duration of stress, and cultivar genetics. Salinity also causes oxidative damage as a consequence of producing large Dimkpa et al (2009) reported that rhizosphere microorganisms, exclusively beneficial bacteria and fungi, can improve plant performance under stress environments and enhance yield. The use of PGPR may be proper in developing strategies to facilitate plant growth in saline soils (Vessy, 2003).…”
Section: Introductionmentioning
confidence: 99%